Characteristics and modifications of the sexuality during pregnacy - Sofía Piñero Navero; Granada Alarcos Merino; María Tania Arenas Orta; Virginia Jiménez Iglesias; Eva María Ortega Ballesteros; María José Ramiro Figueroa (Fundación para el Desarrollo de la Enfermería, 2011)
Objectives: To describe the changes that take place (are produced) in the sexuality of the woman during the pregnancy. To study aspects related to the sexual education.Material and method: The study consisted of a descriptive transverse analysis, obtaining the information across a questionnaire with 32 articles, elaborated from a study of others realized previously, after a bibliographical review for such a purpose. Our study was realized to a whole of 103 participants. The sample divided in three quarters of pregnancy. There were gathered information of filiation, studies, socioeconomic and cultural level of the couple, age, duration of the living together, problems and sexual habits and sexual received education.Outcomes: The sexual interest remains constant during the first and second quarter, diminishing in the third one. In general, the sexual relations suffer a decrease along the pregnancy (embarrassment), being more marked in the third quarter, though practically they all are satisfied and consent to his (her, your) sexual life, without forgetting that a part of the polled ones increases his (her, your) interest and improves his (her, your) sexual life.Conclusions: We must affect in the importance of a major sexual education during this period for sanitary qualified personnel.Other studies demonstrate that a better educational level and the fact of having a stable couple diminish the sexual dysfunctions.We must insist on the option not coital for the intimate expression and the enrichment of the couple.